Pengaruh Literasi Keuangan dan Sikap Keuangan Terhadap Pengelolaan Keuangan pada Pengusaha Perempuan Desa Sembiran - Savitri, Komang Trisna; Santi, Ni Wayan Ayu (Universitas Pendidikan Ganesha, 2025)
The purpose of this research is to analyze the influence of financial literacy and financial attitude on financial management among female entrepreneurs in Sembiran Village. The research method used is quantitative with a saturated sampling technique involving 113 female entrepreneurs. Data analysis was conducted using multiple linear regression analysis techniques. The results of the study indicate that, (1) financial literacy has a positive and significant effect on financial management, with a significance level of 0.000 < 0.05. (2) Financial attitude also has a positive influence with a significance level of 0.000 < 0.05. (3) Simultaneous analysis of the variables of financial literacy and financial attitude on financial management shows a positive and significant influence on financial management, as evidenced by F count (38.625) > F table (3.080) at a significance level of 0.000 < 0.05. This result shows that the independent variables have an effect, both partially and simultaneously, on the dependent variable, namely financial management among female entrepreneurs in Sembiran Village.